Online social media — a vehicle for city branding in China: the case of Sponge City Program (SCP) - Thadani, Dimple; Li, Lei; Chan, Faith Ka Shun (Springer, 2020)
The shift of academic attention from city marketing to city branding heralds a new era of representation and signification of cities as brands. Conscious practices of nationwide program implementation could be used not only for improving urban resilience but for city brands promotion. In China, to cope with the frequent occurrence of urban water issues, a nationwide initiative called Sponge City Program (SCP) has been launched since 2013. Given the significant impact of online social media on brand image, various levels of the Chinese Governments have begun to use online social media for city program promotion. In particular, brand community formed by stakeholders on online social media can significantly influence the brand image by co-creating contents. In this paper, we first analyze the current application of online social media for city marketing in China based on the SCP implementation. Next, we propose a framework/typology to inform how Chinese’ social media could be used for effective city branding. Finally, we conclude by discussing the implications of online social media use in China.